Elevating Learning Independence: Contextual Teaching and Learning Through Media Development Video Tutorials - Juwita, Reci; Erita, Selvia; Gunawan, Rilla Gina (Insitut Agama Islam Negeri Kerinci, 2023)
This study aims to determine the validity of video tutorials based on Contextual Teaching and Learning for independent learning. To know the practicality of video tutorials based on Contextual Teaching and Learning for independent learning. To find out the effectiveness of video tutorials based on Contextual Teaching and Learning for independent learning seen from the responses of students. The type of research used in this research is research and development (Research and Development). The development model used in this research is the development model according to Isman in 2011 which consists of five stages, namely input, process, output, feedback and learning. The subjects in this study were class VIII students of SMP Negeri 4 Sungai Full in the odd semester of the 2021/2022 academic year. Field trials were carried out in one class, namely class VIII D. The results showed that the validity of the media was 1.00 and the validity of the material was 1.00. Based on the results of the practicality analysis, video tutorial media based on Contextual Teaching and Learning for independent learning is said to be practical with a practical result of video tutorial media of 10.75 with a percentage of 83% in the practical category. The effectiveness of the video tutorial media developed is said to be effective for observing student learning independence. It can be seen from the students' responses to learning mathematics using video tutorial media based on Contextual Teaching and Learning for learning .independence fulfilling the